The Impact of COVID-19 on the Teaching Work: From Face-to-Face to Virtual - Juan Méndez Vergaray, Edward Flores, Cristina Asuncion Lopez Ulloa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this review is to analyze the publications on the impact of COVID-19 on the virtual work of teachers in relation to work, socio-family and mental health. To review the literature, 32 articles were examined in the following databases: Scopus, EBSCO and Scielo; in English and Spanish, between 2020-2021. The search terms were: "teachers AND Covid-19", "impact of Covid-19 on teachers", "mental health AND teachers", "stress AND COVID-19", "family AND COVID-19". In addition, for the analysis of the results, 14 articles were considered and organized in a data matrix considering the aspects: work life, socio-family and mental health of teachers; framed in the COVID-19 context. As a result, in one study, 36.1% of teachers indicated that they were moderately satisfied with their work because they were not prepared to take on virtual education. Likewise, other authors found that levels of stress and distress were increasing, reaching very serious levels. Consequently, studies carried out on the impact of COVID-19 on teachers' work show that it has significantly affected their daily educational work, but that teachers have found coping strategies to deal with this new social and pedagogical dynamic.